PEMANFAATAN E-CRM SEBAGAI PENDUKUNG AKTIVITAS PENJUALAN DAN LAYANAN DALAM BUTIK BETY DAN BUDI - Adinda Siti Rahmah Sinaga; Guntur Maha Putra; Sudarmin (LPPM Universitas Abdurrab, 2026)
Butik Bety and Budi is a fashion retail business that still manually records transactions using books, resulting in product data, customer information, and purchase history not being digitally integrated. This condition leads to inefficient data management and reporting processes. This study aims to develop a web-based Electronic Customer Relationship Management (E-CRM) system to support sales and customer service activities at Butik Bety and Budi. This research uses a qualitative approach with data collection techniques through observation, interviews, and literature review. The system was developed using the PHP programming language and MySQL database and was designed using Unified Modeling Language (UML). System testing was conducted using the Black Box Testing method. The results show that all system functions operated according to the testing scenarios with a 100% success rate. The developed system integrates customer, product, and transaction data into a centralized platform, thereby improving sales process efficiency and supporting more effective customer relationship management.